Foundations of environmental sustainability the coevolution of science and policy - Rockwood, Larry L., 1943-; Stewart, Ronald E. (Ronald Eugene), 1943-; Dietz, Thomas (Oxford : Oxford University Press, 2008)
The contributors to this book review and analyze the period (roughly from the 1950s to the present) when the 'environment' became an issue as important as economic growth, or war and peace. The aim is to assess the current situation, and begin planning for the challenges that lie ahead.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental policy -- United States; Environmental monitoring -- United States; Sustainable development -- United States